Analisis Peranan Guru, Lingkungan, dan Teknologi terhadap Pembentukan Moral Generasi Z melalui Pendidikan Agama Islam - Rudi Hartono; Rostinah Rostinah; Syahrianti Syahrianti (ALSYS, 2026)
Although the formation of students’ morals through Islamic Religious Education has received attention in various studies, studies that specifically discuss the interconnected roles of teachers, the social environment, and digital technology in the moral formation of Generation Z remain limited. This study aims to analyze the roles of Islamic Religious Education teachers, the environment, and technology in the moral formation of Generation Z among students. This study employed a qualitative approach with a descriptive study design, involving three participants consisting of one Islamic Religious Education teacher and two students of class XII A selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that Islamic Religious Education teachers have a primary role in students’ moral formation through role modeling, habituation, and the provision of advice. The family environment and students’ peer associations also influence the habituation of moral behavior, whereas digital technology has a dual influence as a learning medium as well as a challenge to students’ moral development. These findings contribute to the development of social learning theory and broaden understanding of the relevance of Islamic Religious Education in the context of the digital generation. This study concludes that synergy among teachers, the environment, and the use of technology is very important in supporting students’ moral formation, so schools and families need to strengthen collaboration in fostering students’ character. The implications of this study include theoretical contributions to enriching Islamic Religious Education studies and practical contributions for educational institutions in designing learning strategies that are more adaptive to technological developments, while also opening opportunities for further research in broader school contexts.